Photoacclimation and entrainment of photosynthesis by fluctuating light varies according to genotype in Arabidopsis thaliana - Burgess, Alexandra J.; Retkute, Renata; Murchie, Erik H. (Frontiers in Plant Science, 2023)
Acclimation of photosynthesis to light intensity (photoacclimation) can take hours or days to achieve and so naturally fluctuating light presents a potential challenge where leaves may be exposed to light conditions that are beyond their window of acclimation. Experiments generally have focused on unchanging light with a relatively fixed combination of photosynthetic attributes to confer higher efficiency in those conditions. Here a controlled LED experiment and mathematical modelling was used to assess the acclimation potential of contrasting Arabidopsis thaliana genotypes following transfer to a controlled fluctuating light environment. The fluctuating light pattern was designed to present frequencies and amplitudes more relevant to natural conditions. We hypothesise that acclimation of light harvesting, photosynthetic capacity and dark respiration are controlled independently. Two different ecotypes were selected, Wassilewskija-4 (Ws), Landsberg erecta (Ler) and a GPT2 knock out mutant on the Ws background (gpt2-), based on their differing abilities to undergo dynamic acclimation i.e. at the sub-cellular or chloroplastic scale. We present evidence that during such conditions plants can independently regulate different components that could optimise photosynthesis in both high and low light; targeting light harvesting in low light and photosynthetic capacity in high light. Second we used a modelling approach to show the pattern of ‘entrainment’ of photosynthetic capacity by past light history is genotype-specific. These data show flexibility of photoacclimation and variation useful for plant improvement.